Causas múltiplas de morte relacionadas ao HIV/AIDS nos municípios de São Paulo e Santos, 2001 - Claudia Cristina de Aguiar Pereira (2005)
The purpose of the present study is to investigate mortality related to HIV/AIDS from a multiple cause-of-death perspective, considering all death causes mentioned in the 2001 death certificates of those individuals who died from HIV/AIDS related causes, and were residents of two Brazilian Cities: São Paulo and Santos. Both Cities are located in São Paulo state, the former is the states capital. HIV/AIDS is a chronic and infectious disease, for which no cure currently exists. São Paulo and Santos are considered important cities for studying the HIV/AIDS epidemic in Brazil, given the high prevalence of the disease in these two localities.The main objective of this research is to use all causes of death related to HIV/AIDS to create profiles of death causes. This objective is accomplished through the use a fuzzy multivariate technique, known as Grade of Membership (GoM). This technique allows the examination of the multiple causes of death related to HIV/AIDS. The results indicate that there are three different profiles of mortality. The first refers to death causes usually observed before the introduction of the Highly Antiretroviral Therapy (HAART), marked by the presence of opportunistic infections. The second profile has mixed characteristics of death causes, with characteristics from both the pre and post- HAART periods. The third profile is a residual one, but contains important groups of death causes that are important in the study of the HIV/AIDS mortality.This study aims to contribute to the understanding of the new scenario of morbidity-mortality related to HIV/AIDS in order to improve the treatment services and care offered by the public health service providers. It is important to emphasize that in this new scenario it is possible to observe the coexistence of the old well-known opportunistic infections related to AIDS along with the new morbidities related to the utilization of the HAART therapy.